PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID BERMUATAN KEARIFAN LOKAL PADA MATERI GERAK DI MASA NEW NORMAL COVID-19 KELAS VIII SMP NEGERI 1 LEDO - Widya Yuliatin Riski (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
The purpose of this study was to determine the development and feasibility of Andriod-based learningmedia containing local wisdom according to material experts, the feasibility of Andriod-based learning mediacontaining local wisdom according to media experts, and knowing student responses to Andriod-based learningmedia containing local wisdom. This type of research is research (R & D) in the form of an Android-based learning media product containing local wisdom on motion material. The development method used in this research is the ADDIE model. The ADDIE model is a development model consisting of five stages consisting ofanalysis, design, development, implementation and evaluation. Based on the results of the research that 1) Thefeasibility of android-based learning media containing local wisdom can be seen from the results of the assessmentof material experts getting an average score of 85% with very decent criteria; 2) The feasibility of android-basedlearning media containing local wisdom can be seen from the results of the assessment of media experts getting anaverage score of 90% with very decent criteria; 3) Student responses to the use of android-based learning mediacontaining local wisdom obtained an average score of 81% with the criteria of strongly agreeing. Thus theandroid-based learning media containing local wisdom in the motion material developed is considered suitable tobe used as a learning medium.